The down-deep delight of democracy - Purcell, Mark (Wiley-Blackwell, 2013)
Arguing that the hegemony of the neoliberal/capitalist nexus must be challenged if we are to address the proliferating challenges facing our world, this inspiring book explains how democracy can revive the political fortunes of the left. Explores issues central to the civil uprisings that swept the world in 2011, drawing profound connections between democracy and neoliberalism in an urban contextFeatures in-depth analysis of key political theorists such as Gramsci; Lefebvre; Rancière; Deleuze and Guattari; and Hardt and Negri.